Intraparenchymal Hematoma as the Beginning of an Arteriovenous Malformation. Case Report - Juan Ibrahim García Leonard; Ada Sánchez Lozano; Masleidy Valladares Valle (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Cerebral arteriovenous malformations are vascular abnormalities characterized by a fistulous connection between arteries and veins without the intervention of the normally existing capillary bed. They are frequently located in the territory of the great cerebral arteries, but they can appear in any other vascular bed and are causes of intracerebral hemorrhages, epilepsy, focal neurological signs, and other symptoms. A case of a 64-year-old female patient, hypertensive and diabetic, who acutely presented with left hemicorporal weakness, is presented. On physical examination, she had dysarthria, left hemiparesis and meningeal signs. The initial computed tomography scan showed a right parietooccipital intraparenchymal hematoma opening to the ventricular system. CT angiography showed right parietooccipital cerebral arteriovenous malformations. Treatment of this condition depends on patient factors, as well as angiographic factors. The different options are: watchful waiting, symptomatic medical treatment, surgical resection, endovascular therapy, stereotaxic radiosurgery. The clinical case of an intraparenchymal hematoma secondary to a cerebral arteriovenous malformation is presented because it is a rare condition in an older adult.